DRIVING ACADEMIC ADVANTAGE THROUGH VALUES-BASED EMPLOYEE PERFORMANCE: THE INTERPLAY OF LEADERSHIP STYLE, WORK MOTIVATION, AND JOB SATISFACTION - Hasnawati Hasnawati; Rahmad Hidayat; Najmi Diyana Lathifah; Sukatin Sukatin; Saifaldin Idris Onia (Nurul Jadid University, Paiton Probolinggo, East Java, 2026)
This study aimed the relationships between leadership style, work motivation, job satisfaction, and value-based employee performance at the Faculty of Tarbiyah and Teacher Training. Value-based employee performance is a strategic concern in Islamic higher education because it supports academic service quality, administrative effectiveness, ethical service orientation, and institutional excellence. This study employed a quantitative descriptive-correlational survey design. The population consisted of all 48 faculty employees, including program chairs, educational support staff, cleaning personnel, and security personnel. Because the population was fewer than 100, total sampling was applied. Data were collected through a closed-ended questionnaire using a four-point Likert scale and analyzed using descriptive statistics, Pearson correlation, and the coefficient of determination. The findings show that leadership style was positively and significantly associated with value-based employee performance (r = 0.379; p = 0.008). Work motivation also showed a positive and significant association with value-based employee performance (r = 0.421; p = 0.003). Job satisfaction had the strongest positive correlation with value-based employee performance (r = 0.529; p = 0.000). The coefficient of determination was R² = 0.143, indicating that leadership style, work motivation, and job satisfaction collectively explained 14.3% of the variance in value-based employee performance. The implication of these findings is that enhancing value-based employee performance in Islamic higher education institutions requires participatory leadership, stronger motivational support, sustained job satisfaction, and an ethical service culture grounded in Islamic academic values.